SOSIALISASI INTERNET SEHAT SEBAGAI UPAYA PENCEGAHAN PENGGUNAAN KONTEN PORNOGRAFI DI INTERNET BAGI PEMUDA PEMUDI GEDONGKUNING, TEGALTANDAN, BANGUNTAPAN, BANTUL - Prita Haryani; Erma Susanti (Universitas Sahid Surakarta, 2018)
The Internet can be a place for young people to do creativity and innovation. The phenomenon of widespread use of social media, especially among adolescents (10-24years) has a positive and negative impact on the development of adolescents today.Community Service Activities is a response from lecturers to the conditions orphenomena that exist in these communities. The influence of negative content on theInternet is the reason why socialization is necessary, the introduction of good and ageappropriate internet usage and knowing prevention ways and techniques so youth canovercome and counteract the perilous dangers of negative content.Healthy Internet Socialization is held in Hamlet Tegaltandan, Banguntapan Village, District Banguntapan, Bantul regency. Expected by the socialization of InternetHealthy, adolescents are expected to utilize the Internet wisely and can filter the information obtained. IT knowledge is very necessary for adolescents to be able toequip themselves in using the Internet network either on PC or Smart Device (smart phone).